Alliance curse : how America lost the Third World - Root, Hilton L. (Brookings Institution Press, 2008)
"Proposes an analytical foundation for national security that challenges long-held assumptions or outdated suppositions about foreign affairs. Presents case studies of American foreign policy toward developing countries, efforts at state building, and nations growing in importance. Concludes with recommendations designed to close the gap between security and economic development"--Provided by publisher